Copper Oxide Nanoparticle Diameter Mediates Serum‐Sensitive Toxicity in BEAS‐2B Cells. Issue 4 (22nd February 2021) - Morris, Angie S.; Givens, Brittany E.; Silva, Aaron; Salem, Aliasger K.
Abstract : Copper oxide (CuO) nanoparticles (NPs) are abundant in manufacturing processes, but they are an airway irritant. In vitro pulmonary toxicity of CuO NPs has been modeled using cell lines such as human bronchial epithelial cell line BEAS‐2B. In 2D in vitro culture, BEAS‐2B undergoes squamous differentiation due to the presence of serum. Differentiation is part of the repair process of lung cells in vivo that helps to preserve the epithelial lining of the respiratory tract. Herein, the effects of serum on the hydrodynamic diameter, cellular viability, cellular differentiation, and cellular uptake of 5 and 35 nm CuO NPs are investigated, and the mean cell area is used as the differentiation marker for BEAS‐2B cells. The results demonstrate that the hydrodynamic diameter decreases with the addition of serum to the culture medium. Serum also increases the mean cell area, and only affects dose‐dependent cytotoxicity of 35 nm CuO NPs, while simultaneously having no effect on intracellular Cu 2+ . This study presents evidence that both NP size and the presence of serum in culture media influence the relative viability of BEAS‐2B cells following CuO NP exposure and highlights a critical need for carefully designed experiments and accurately reported conditions. Abstract : Copper oxide nanoparticles (CuO NPs) of 5 and 35 nm diameter are administered to the bronchial epithelial cell line BEAS‐2B in vitro. The 35 nm CuO NPs have a greater negative effect on relative cell viability as both a function of fetal bovine serum (FBS) concentration in media and Cu 2+ concentration.